(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Survey the prevalence of traditional medicine syndromes and characteristics of syndrome-specific symptoms in patients with herpes zoster (HZ). Methods: Descriptive cross-sectional study. Results: Three syndromes were identified in patients with shingles. The most prevalent was Liver meridian stagnation and heat syndrome, accounting for 67.5%, followed by Spleen deficiency and dampness accumulation syndrome at 20%, and Qi stagnation and blood stasis syndrome at 12.5%. Conclusion: Three traditional medicine disease syndromes were surveyed. The most common syndrome was Liver meridian stagnation and heat syndrome, followed by Spleen deficiency and dampness accumulation syndrome, and finally Qi stagnation and blood stasis syndrome